A Difícil Construção da Cidadania no Brasil - Dejalma Cremonese (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2007)
This article presents an overview about the difficult citizenship construction in Brazil. Understood and utilized in different ways along (the) history, (the) citizenship is essentially connected to the conquests of rights. For the Greeks, it represented the equality between the citizens (men), the right to participate in the Polis and the exercise (the) of democracy; for moderns it was connected to the right to life, freedom, property and the universal suffrage (civil and political rights); in the developed societies of the 20th century, the conquest cycle got completed with the social rights. In Brazil, the conquest of rights did not follow the logic nor the chronological time of the developed societies: here, the individual and political rights appeared delayed (1824), finally, the social rights were conquered (the 30´s and 60´s), exactly when the civil and political rights were denied.